The median effective concentration of epidural ropivacaine with different doses of dexmedetomidine for motor blockade: an up-down sequential allocation study - Wan, Ji-Xiang; Lin, Chao; Wu, Zhi-Qiang; Feng, Duan; Wang, Yuan; Wang, Fang-Jun (Frontiers in Medicine, 2024)
Study objective Recent studies have shown that dexmedetomidine can be safely used in peripheral nerve blocks and spinal anesthesia. Epidural administration of dexmedetomidine produces analgesia and sedation, prolongs motor and sensory block time, extends postoperative analgesia, and reduces the need for rescue analgesia. This investigation seeks to identify the median effective concentration (EC50) of ropivacaine for epidural motor blockade, and assess how incorporating varying doses of dexmedetomidine impacts this EC50 value. Design Prospective, double-blind, up-down sequential allocation study. Setting Operating room, post-anesthesia care unit, and general ward. Interventions One hundred and fifty patients were allocated into five groups in a randomized, double-blinded manner as follows: NR (normal saline combined with ropivacaine) group, RD0.25 (0.25 μg/kg dexmedetomidine combined with ropivacaine) group, RD0.5 (0.5 μg/kg dexmedetomidine combined with ropivacaine) group, RD0.75 (0.75 μg/kg dexmedetomidine combined with ropivacaine) group, RD1.0 (1.0 μg/kg dexmedetomidine combined with ropivacaine) group. The concentration of epidural ropivacaine for the first patient in each group was 0.5%. Following administration, the patients were immediately placed in a supine position for observation, and the lower limb motor block was assessed every 5 min using the modified Bromage score within 30 min after drug administration. According to the sequential method, the concentration of ropivacaine in the next patient was adjusted according to the reaction of the previous patient: effective motor block was defined as the modified Bromage score > 0 within 30 min after epidural administration. If the modified Bromage score of the previous patient was >0 within 30 min after drug administration, the concentration of ropivacaine in the next patient was decreased by 1 gradient. Conversely, if the score did not exceed 0, the concentration of ropivacaine in the next patient was increased by 1 gradient. The up-down sequential allocation method and probit regression were used to calculate the EC50 of epidural ropivacaine. Measurements Adverse events, hemodynamic changes, demographic data and clinical characteristics. Main results The EC50 of epidural ropivacaine required to achieve motor block was 0.677% (95% CI, 0.622–0.743%) in the NR group, 0.624% (95% CI, 0.550–0.728%) in the RD0.25 group, 0.549% (95% CI, 0.456–0.660%) in the RD0.5 group, 0.463% (95% CI, 0.408–0.527%) in the RD0.75 group, and 0.435% (95% CI, 0.390–0.447%) in the RD1.0 group. The EC50 of the NR group and the RD0.25 group were significantly higher than that of the RD0.75 and the RD1.0 groups, and the EC50 of the RD0.5 group was significantly higher than that of the RD1.0 group. Conclusion The EC50 of epidural ropivacaine required to achieve motor block was 0.677% in the NR group, 0.624% in the RD0.25 group, 0.549% in the RD0.5 group, 0.463% in the RD0.75 group, and 0.435% in the RD1.0 group. Dexmedetomidine as an adjuvant for ropivacaine dose-dependently reduce the EC50 of epidural ropivacaine for motor block and shorten the onset time of epidural ropivacaine block. The optimal dose of dexmedetomidine combined with ropivacaine for epidural anesthesia was 0.5 μg/kg.